Persepsi Pemustaka Terhadap Ketersediaan Koleksi di UPT Perpustakaan Kopertis Wilayah X - Susanti, Vivi; Desriyeni, Desriyeni (Program Studi Informasi, Perpustakaan, dan Kearsipan , Jurusan Bahasa dan Sastra Indonesia, 2015)
This paper aims to describe: user perception of the availability of the collection at the Library Unit Kopertis Region X. The data were collected through observation and quantitative researchby distributed questionnaire (questionnaire) to every visitor UPT Library Kopertis Region X. Samplesused for 52 (fifty-two) respondents. Analyzing datatotabulate the results of respondents' answersinto the list of tabulationand the questionnaire result swith normal analysis techniques. Based on data analysis can be concluded that user not satisfied with the collection available as: collection available in the Library Kopertis Region X is still the most (up to date) with parsentase 42,3%, neatness in the preparation parsentase collection by 67,3%, collections provided incomplete with parsentase 82,6%, in the search user not get the book easily with parsentase 50%, the collection is available yet with the times with parsentase 51,9%, the collection is available not in accordance with the needs pemustaka with parsentase 40, 3%, the collection of which there are many that are not suitable to be used with parsentase 34,6%; libraries must make additions to the collection parsentase 94,2%, services librarian to user with parsentase 57.6%, the cleanliness of the collection has not been clean with parsentase 67,3%. Keywords: user not satisfied, collectionis not complete.